Teknologi RANCANG BANGUN KONTRUKSI TUBULAR CHASSIS PADA WIKAN ELEKTRIC TACTICAL VEHICLE : Otoranpur - Wahyu, Dwiky; Hendro, Farid (Pustaka Poltekad, 2024)
Abstract: Thoroughly on the design of the chassis construction mathematical and analysis using Ansys software. The data obtained is the stress that occurs in the construction of tubular chassis of the middle part is and the stress in the construction of tubular chassis of the rear is , the safety factor resulting from the calculation of the structure of the center tubular frame is 13, and the structure of the rear tubular frame has a safety factor value of 2. The results of the calculation of the design of the tubular chassis can be declared safe because the lowest value of the safety factor is 2. The results of the analysis of the design of the tubular chassis include several factors, the factors resulting from the analysis in Ansys software are total deformation, equivalent stress and safety factor. The results of the total deformation in the tubular chassis construction amounted to 2.3948mm, and the equivalent stress of the tubular chassis construction amounted to 209.35MPa, and the value of the safety factor on the tubular chassis construction amounted to 15, from these results, the analysis on the tubular chassis frame is declared safe because the resulting value of the safety factor is greater than 2. Keywords: Konstruction,Materials Abstrak: Secara menyeluruh tentang perancangan konstruksi chassis secara matematis dan analisis menggunakan software ansys. Adapun data yang diperoleh adalah tegangan yang terjadi pada konstruksi tubular chassis bagian tengah adalah dan tegangan pada konstruksi tubular chassis bagian belakang adalah , safety factor yang dihasilkan dari perhitungan konstruksi tubular chassis bagian tengah adalah 13 serta konstruksi tubular chassis bagian belakang memiliki nilai safety factor sebesar 2. Hasil perhitungan pada konstruksi tubular chassis dapat dinyatakan aman karena nilai terendah safety factor adalah 2. Adapun hasil analisis yang dihasilkan pada konstruksi tubular chassis adalah meliputi beberapa faktor, faktor yang dihasilkan dari analisis pada software ansys adalah total deformasi, equivalent stress dan safety factor. Hasil total deformasi pada konstruksi tubular chassis sebesar 2,3948mm dan equivalent stress konstruksi tubular chassis sebesar 209,35 Mpa serta nilai safety factor pada komstruksi tubullar chassis sebesar 15, dari hasil tersebut analisi pada rangka tubullar chassis dinyatakan aman karena nilai safety factor yang dihasilkan lebih besar dari 2.